Volatiles from cotton aphid (Aphis gossypii) infested plants attract the natural enemy Hippodamia variegata - Yi, Chaoqun; Teng, Dong; Xie, Jiaoxin; Tang, Haoyu; Zhao, Danyang; Liu, Xiaoxu; Liu, Tinghui; Ding, Wei; Khashaveh, Adel; Zhang, Yongjun (Frontiers in Plant Science, 2023)
The Aphis gossypii is a major threat of cotton worldwide due to its short life cycle and rapid reproduction. Chemical control is the primary method used to manage cotton aphid, which has significant environmental impacts. Therefore, prioritizing eco-friendly alternatives is essential for managing cotton aphid. Hippodamia variegata is a predominant predator of cotton aphid. Its performance in cotton plantation is directly linked to chemical communication, where volatile compounds emitted from aphid-infested plants play important roles in successful predation.Through behavioral tests, this study initially demonstrated the clear preference of both larvae and adults of H. variegata for aphid-infested plants. Subsequently, 13 compounds, namely α-pinene, cis-3-hexenyl acetate, 4-ethyl-1-octyn-3-ol, β-ocimene, dodecane, E-β-farnesene, decanal, methyl salicylate, β-caryophyllene, α-humulene, farnesol, DMNT, and TMTT were identified from aphidinfested plants. All these compounds were electrophysiologically active and induced detectable EAG responses in larvae and adults. Y-tube olfactometer assays indicated that all identified chemicals were attractive to H. variegata, particularly at the highest tested concentration (100 mg/ml). The outcomes of this study establish a practical foundation for developing attractants for H. variegata and open avenues for potential advancements in aphid management strategies by understanding the details of chemical communication at a tritrophic level.